1976
DOI: 10.1017/s0016672300016463
|View full text |Cite
|
Sign up to set email alerts
|

Macronuclear DNA in Stentor coeruleus: a first approach to its characterization

Abstract: SUMMARYThe macronuclei of Stentor coeruleus were isolated on a discontinuous sucrose gradient and their DNA was purified by conventional methods. The GC content was 32 mole %. The DNA banded as a single peak on analytical ultracentrifugation at 1-691 g/cm 3 . The molecular weight of the DNA was 5 x 10 6 to 4 x 10 7 daltons. Genome size determined by DNA-DNA reassociation kinetics was 6 x 10 10 daltons. The macronuclear genome was mostly simple, about 85 % being made of non-repetitive sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
7

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
3
2
0
7
Order By: Relevance
“…It is important to note that contigs could lie outside the range we identified experimentally. The size of the Stentor genome has previously been estimated at approximately 92Mb [7], similar to our estimate of 83 Mb. Considering the high level of alignment of cDNA reads with our genome (see below) we suspect that our assembly is mostly complete and that the biochemical estimates may have overestimated genome size slightly.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…It is important to note that contigs could lie outside the range we identified experimentally. The size of the Stentor genome has previously been estimated at approximately 92Mb [7], similar to our estimate of 83 Mb. Considering the high level of alignment of cDNA reads with our genome (see below) we suspect that our assembly is mostly complete and that the biochemical estimates may have overestimated genome size slightly.…”
Section: Resultssupporting
confidence: 86%
“…The contig size distribution is consistent with prior biochemical analysis of isolated Stentor genomic DNA, in which it was estimated that 50% of the genome consisted of chromosomes in the 46–62 kb range [7]. We further investigated the distribution of chromosome sizes using a CHEF gel (Figure S1 D) and found that the range of sizes is 20kb – 250kb, comparable to the range of sizes of contigs in the assembly (250b–265kb).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…DNA was isolated by a modification of Pelvat's method (Pelvat and DeHaller 1976). Cells were washed by photodispersal by, a modification of a method originally described by Dr. Vance Tartar (Tartar, 1961).…”
Section: Methodsmentioning
confidence: 99%
“…The macronuclear DNA of Stentor coeruleus (order Heterotrichida and separated from Tetrahymena species and hypotrichs by very large genetic distances) appears to occur in subchromosomal fragments. Most DNA ranges from 7.5 to 60 kbp as determined by sucrose gradients and 45 to 75 kbp by electron microscopy (261). Macronuclear DNA in two cyrtophorid ciliates, Trithigmostoma and Chilodonella species, which are very distant relatives of hypotrichs, ranges in size from 0.35 to -70 kbp with an average size of 4 kbp and with numerous bands in electrophoretic gels, presumably representing particular, differentially amplified molecules (195,229).…”
Section: Micronuclear and Macronuclear Dnasmentioning
confidence: 99%